2018
DOI: 10.1111/apce.12202
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Measurement and Conceptual Frameworks: A Review of the Literature

Abstract: The lack of consensus and consistency in measuring resilience undermines the ability of the development aid community to objectively monitor and verify the effects of programs that are intentionally designed to build resilience. In this paper we compare conceptual and analytical models of resilience used by various development organizations, critically evaluating their strengths and weaknesses from a program implementation and measurement point of view. We provide the reader with a clear synthesis of the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…Empirical studies published in recent years diverge on the operationalization and methodological measurement of resilience, thus yielding outcomes which are hardly comparable. Such heterogeneity challenges scientific progress and does little help to properly inform policy and investment decisions (Serfilippi and Ramnath 2018). The heterogeneous results also raise the question of whether these studies measure the same concept with different methods or measure different things and refer to it as resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies published in recent years diverge on the operationalization and methodological measurement of resilience, thus yielding outcomes which are hardly comparable. Such heterogeneity challenges scientific progress and does little help to properly inform policy and investment decisions (Serfilippi and Ramnath 2018). The heterogeneous results also raise the question of whether these studies measure the same concept with different methods or measure different things and refer to it as resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we assess whether the studies identified indeed operationalize and measure the relationship between resilience and food security. Serfilippi and Ramnath (2018) provide a literature review of the research on resilience in general as applied by humanitarian organizations. Our paper extends their work in two main respects.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we embrace the capacity approach initiated by Béné (2012Béné ( , 2015, and followed by Frankenberg and Smith (2018), Serfilippi and Ramnath (2017); Knippenberg et al (2019). In this approach, absorptive capacity is a household's ability to absorb the impacts of shocks in the short-run.…”
Section: Resilience Conceptual Frameworkmentioning
confidence: 99%
“…The interaction between these capacities guarantees the stability, flexibility, and change of a system after a large covariate shock (Serfilippi and Ramnath, 2017). The ideal outcome of the absorptive capacity is to offer resistance to a shock.…”
Section: Resilience Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation